The Behavior Of Adolescent Reproductive Health Facility Utilization - Lisa Purbawaning Wulandari; Tarsikah Tarsikah; Gita Kostania (Poltekkes Kemenkes Surakarta, 2022)
Background: Adolescence is the starting point of the human life cycle in preparing for a healthy reproductive process. Guidance and information that is not true at this time can oftaffectect the future of adolescents. Most adolescents don’t use Adolescent Reproductive Health (ARH) services (57%), quite a lot of adolescents (46.3%) use internet technology in accessing the information on ARH (Sampulawa & Mubarokah, 2015). Based on the above background, the researcher wants to explore the behavior of using ARH facilities in the city of Malang. Methods: Descriptive research method with cross-sectional approach, with population, are all teenagers in the city of Malang. The research sample was taken using the purposive sampling technique, obtained a suitable sample of 200 adolescents from April to June 2021. The inclusion criteria of this study were unmarried and willing to be research respondents. Collecting data using a questionnaire via a google form. Descriptive analysis technique, presented in the frequency distribution. Results: The majority of respondents have never received correct knowledge about reproductive health (89.6%), with the majority of information sources obtained from schools (80%) and mass media (45.5%). Respondents used mass media to access information on reproductive health from the internet (87.5%) and books (51.5%). In using gadgets, respondents use them for 5-10 hours a day (53.5%), but only occasionally use them to find information about reproductive health (50.5%). Respondents stated that the use of mass media as a source of information about reproductive health can help in maintaining health (96.5%). Conclusion: Internet-based health education about adolescent reproductive health is needed because it is easy and simple, and the content is interesting to read. It can be used as an alternative media for reproductive health learning.